Towards better service in restaurants by monitoring trends: Display of nutritional values on the menus - Ivkov Milan (University Educons, Faculty of Sports and Tourism, Novi Sad, 2015)
Business obligations, the manner and pace of life today, and a large number of options when it comes to eating out, require that at least one meal is consumed outside the residence or using the services of catering and retail facilities. With this in mind, restaurants are forced to fight in the market and to differentiate the specific offer to attract a particular segment of the market. Differentiation is possible through monitoring the trends and timely adjustments to more demanding consumer needs. In this way, restaurateurs also contribute to greater customer satisfaction through quality service, which also has a positive effect on the restaurant and sales performance. Based on the results of the survey of 82 respondents, it was concluded that nutritional information shown within menus is of no importance, and also that such information does not affect the selection of dishes. Although nutritional information can be helpful in selecting more favourable and healthy food, neither men nor women care about it.